ANALISIS KETEBALAN ENDAPAN LATERIT DAN PENGARUHNYA TERHADAP KADAR NIKEL DI DAERAH KONINIS, KABUPATEN BANGGAI - Nonsi, Mutiara; Arifin, Yayu Indriati; Akase, Noviar (Universitas Negeri Makassar, 2024)
The Koninis region has diverse morphological features accompanied by the formation of nickel laterite deposits, leading to variations in the thickness of these deposits. The research location is administratively part of Banggai Regency, at coordinates 05°0'10